Apakah Pengetahuan Investasi, Manfaat Investasi, dan Motivasi Investasi Berpengaruh Terhadap Minat Investasi Pasar Modal Pada Gen-Z? - Eden Bill Kenny Lakatua; Oktavian Gilbert Rewah; Frisky Jeremy Kasingku (Universitas Yudharta Pasuruan, 2024)
Abstract This study aims to analyze the influence of investment knowledge, investment benefits, and investment motivation on Gen Z's interest in capital market investments. Data were collected from 223 Gen Z students selected using purposive sampling. Data analysis was performed using multiple linear regression to test the hypotheses. The variables examined include: Investment Knowledge: Measured by 7 statements assessing the respondents' understanding of investments, investment Benefits: Measured by 6 statements evaluating the respondents' perceptions of the benefits gained from investments, investment Motivation: Measured by 8 statements evaluating the respondents' drives and reasons for investing. investment Interest: Measured by 9 statements assessing the extent of respondents' interest in investing in the capital market. The analysis results indicate that both investment knowledge and investment motivation have a positive and significant effect on Gen Z's interest in capital market investments, with p-values < 0.05 and regression coefficients of 0.364 and 0.515, respectively. In contrast, investment benefits did not show a significant effect on investment interest, with a p-value of 0.819. These findings suggest that investment knowledge and motivation are key factors in enhancing Gen Z's interest in capital market investments, while investment benefits do not play a significant role. This study has theoretical and practical implications for understanding the factors influencing investment interest and can be used to design more effective investment education strategies for Gen Z. AbstrakPenelitian ini bertujuan untuk menganalisis pengaruh pengetahuan investasi, manfaat investasi, dan motivasi investasi terhadap minat investasi pasar modal pada Gen Z. Data dikumpulkan dari 223 mahasiswa Gen Z yang dipilih menggunakan metode purposive sampling. Analisis data dilakukan dengan metode regresi linear berganda untuk menguji hipotesis. Variabel yang diuji meliputi: Pengetahuan Investasi: Diukur dengan 7 pernyataan yang mengkaji sejauh mana pemahaman responden mengenai investasi, Manfaat Investasi: Diukur dengan 6 pernyataan yang menilai persepsi responden mengenai keuntungan yang diperoleh dari investasi, Motivasi Investasi: Diukur dengan 8 pernyataan yang menilai dorongan dan alasan responden untuk berinvestasi, Minat Investasi: Diukur dengan 9 pernyataan yang mengukur seberapa besar minat responden untuk berinvestasi di pasar modal. Hasil analisis menunjukkan bahwa pengetahuan investasi dan motivasi investasi memiliki pengaruh positif dan signifikan terhadap minat investasi Gen Z dengan nilai p < 0,05 dan koefisien regresi masing-masing sebesar 0,364 dan 0,515. Sebaliknya, manfaat investasi tidak menunjukkan pengaruh signifikan terhadap minat investasi, dengan nilai p = 0,819. Temuan ini menunjukkan bahwa pengetahuan dan motivasi investasi adalah faktor kunci dalam meningkatkan minat investasi Gen Z di pasar modal, sementara manfaat investasi tidak berperan signifikan dalam hal ini. Penelitian ini memiliki implikasi teoritis dan praktis dalam memahami faktor-faktor yang mempengaruhi minat investasi, serta dapat digunakan untuk merancang strategi edukasi investasi yang lebih efektif untuk Gen Z.